EFEKTIVITAS BIOINSEKTISIDA JAMUR ENTOMOPATOGEN Aspergillus sp TERHADAP MORTALITAS LARVA KUMBANG TANDUK (Oryctes rhinoceros) (Coleoptera : Scrabaidae ) - Guntoro Guntoro; Nuraida Nuraida; Zizi Graci Violita (Jurnal Agro Estate, 2018)
Oil palm (Elaeis guineensis Jacq) is one of important plantations in the Indonesia role economy. Oil palm can be attacked by various pests or diseases from the nursery. One of the important pests is Oryctes rhinoceros. Some control methods are manually, mechanically, chemically and biologically which are environmentally friendly. One of the biological controls of the Oryctes larvae is with Aspergillus sp. This research was conducted at STIPAP Medan in June - July 2017. Treatment of Aspergillus A0, A1, A2, A3, and A4 bioinsecticides, concentrations of 0, 10, 20, 30, and 40 g / l. This study aims to determine the speed of mortality of larvae and concentration of Aspergillus eﬀective. From the results of this study it can be concluded that mortality of O. rhinoceros larvae seen on day 18 after application of Aspergillus sp at the treatment A4 with dose 40 gram Aspergillus sp and Aspergillus sp. eﬀective for controlling the O. rhinoceros larvae with mortality average above 90%.